111Indium-labelled white blood cells in the diagnosis of Felty's syndrome. Issue 1 (January 1982) - Birnie, G G; Eadie, A S; Hosie, C J; Lucie, N P; Watkinson, G
Abstract : The use of isotope scanning of the spleen in conjunction with 51Cr-labelled red blood cells has become an established technique in the evaluation of patients with hypersplenism. As far as we are aware the similar technique using labelled white blood cells to demonstrate splenic sequestration in a neutropenic patient has not been described. We report a case where this technique proved valuable in confirming the diagnosis and in predicting a favourable response to splenectomy.